Laser welding of Cu-Al-Be shape memory alloys: Microstructure and mechanical properties. (15th June 2018) - Oliveira, J.P.; Zeng, Z.; Berveiller, S.; Bouscaud, D.; Braz Fernandes, F.M.; Miranda, R.M.; Zhou, N.
Abstract: Cu-based shape memory alloys are potential substitutes of NiTi shape memory alloys, owing to their lower production costs and recent increase in mechanical properties arising from better control of the microstructure. The development of joining technologies for advanced materials is key to expand to the potential applications of any engineering alloy. In this work, laser welding of single crystal-like Cu-Al-Be shape memory alloys was performed. The microstructure and tensile properties were evaluated to understand the effect of laser welding on the microstructural and mechanical features of the welded joints. Cycling tests performed for a wide range of temperatures revealed that the joints possess extraordinary superelastic recovery after joining, with potential applications in damping devices due to the significant amount of energy that can be absorbed during superelastic deformation. Graphical abstract: Highlights: Successful laser welding of Cu-Al-Be shape memory alloys The joints exhibit excellent superelastic properties. Superelasticity is preserved between −40 and 100 °C. The joints can be used as energy absorptions devices.